The Effect of ICT & Digital Supply Chain (DSC) in Higher Education Institutions - S A M Manzur Hossain Khan; Nurakmal Ahmad Mustaffa; Md. Mamun Habib (International Journal of Supply Chain Management, 2021)
The study identifies the effect of the implementation of information and communication technology-driven digital supply chain (ICT-DSC) model in education institutes. Besides that, the study defines the integration and evaluation criteria of the Digital Supply Chain model in the academic industry. Finally, an integrated model for educational institutes in Bangladesh is developed through the study. This ICT application-based DSC model would formulate a requirement roadmap to express a guideline for the educational technology impact. It would fulfil all relevant stakeholders desire to diminish risks and increase understanding to overcome drawbacks. The study would also propose a systematic methodology that initiates a considerate process for all relevant stakeholders within an academic institution. Technology Acceptance Model (TAM) was adopted as a theoretical framework. To conduct the study, primary data have been collected from 276 stakeholders of academic-industry in Bangladesh who were interviewed about their interest and performance ICT-DSC in educational institutions. As a statistical tool, SPSS was used for pilot test and PLS for data analysis. To elaborate on the current ICT-DSC execution in the academic infrastructure of Bangladesh. Also, this research outcome is to produce an integrated theoretical model for educational institutions in Bangladesh. This is one of the most recent research studies on academic institutions in Bangladesh.